A gestão da hospitalidade sob a perspectiva da humanização dos hospitais: um estudo de caso - Verbist, Cinthia Fusquine (My University, 2014)
The present technique in the hospital practical is demanding even more the complement offered by the subjectivity made by service and the hospitality conditions.The hospitality is configured as an important aspect identified in the satisfaction of the customers of health, what could be verified through the construction of the built Theorycal Reference and also the study of case accomplished together with the São Jose Hospital, located in the city of Ivoti, Rio Grande Do Sul. To evaluate the hospitality in the health institutions three variables had been identified through the study - organizational culture, Physic/ Flux Settlement and Cultural Organization - which had been attributed indications that allow to evaluate the hospitality in the hospitals. The accomplished case study, therefore, had its function of evaluate the Hospitality on the São José Hospital, through interviews and questionnaires with the health related clients, applied questionnaires for the employees and interview with the Institution administrator, verifying the current situation found in the institution and the situation that can be approached, using as a guide the variables presented and its indicators, always aiming satisfaction and well-being of the health clients (patients and relatives/ companions.
A técnica presente nas práticas hospitalares está demandando cada vez mais o complemento oferecido pela subjetividade possibilitada pelo atendimento e condições de hospitalidade. A hospitalidade configura-se como importante aspecto identificado na satisfação dos clientes de saúde, o que pôde ser verificado através do Referencial Teórico construído e também do estudo de caso realizado junto ao Hospital São José, localizado no município de Ivoti, Rio Grande do Sul. Para avaliar a hospitalidade nas instituições de saúde foram identificadas ao longo desse estudo três variáveis - cultura organizacional, arranjo físico/fluxos e estrutura organizacional - para as quais foram atribuídos indicadores que permitem avaliar a hospitalidade nos hospitais. O estudo de caso realizado, portanto, teve como função avaliar a hospitalidade no Hospital São José, através de entrevistas e questionários com os clientes de saúde, questionários aplicados com os funcionários e entrevista com o administrador da instituição, verificando a situação atual encontrada na instituição e a situação a que se pode chegar, tendo como guia as variáveis apresentadas e seus indicadores, visando sempre a satisfação e o bem-estar dos clientes de saúde (pacientes e acompanhantes/familiares).
Keywords: Turismo; Hospitalidade; Hospitais; Cultura organizacional; Arranjo físico/fluxos; Estrutura organizacional; Gestão hospitalar; Tourism; Hospitality; Hospitals; Organizational culture; Physic/flux settlement; Organizational structure; Hospital management